A novel characteristic value correction iteration method. Issue 2 (7th February 2019) - Zhai, Min; Liu, Guolin; Tao, Qiuxiang; Xin, Mingzhen
ABSTRACT: It has greater randomness that the existing characteristic value correction iteration method terminates the iterative progress by artificially setting threshold to acquire the better intermediate estimates than least squares. To address this problem, the novel characteristic value correction iteration method is proposed in this article. Considering the balance between solutions and residuals, L curve drawn to express the correlation of solutions and residuals and the iteration time correspond to the maximum curvature point is chosen as the iteration termination condition to obtain the "optimal" intermediate estimates. Numerical experiment is carried out to demonstrate the correctness of the theoretical analysis.